Cross Section of Stock Returns in Nepal - Joshi, Vishal (Janabhawana Research Journal, 2023)
This paper investigates the significant firm-specific factors that explain the variation in cross section returns of non-financial firms listed in Nepal Stock Exchange (NEPSE). Firm size, book to market equity ratio, debt equity ratio, earning yield, cash flow yield and dividend yield have been tested to find out explanatory power on explaining variation in cross-section returns of non-financial firms. A total of 14non-financial firms has been selected for this research. Among them, 6 were hydropower companies, 3 were manufacturing companies, 2 were tourism companies and 1 was from another sector. Judgmental sampling design is implemented for sampling procedure. Sampling frame and daily stock prices are obtained from official website of NEPSE. Firm-specific accounting data is collected from annual reports of listed companies. Descriptive, correlational, and analytical research designs are used to explore the research question. A multiple linear regression model was used for data analysis and it was found that only cash flow yield and dividend yield are found to be significant predictors explaining the variation in cross-section returns of non-financial firms listed in NEPSE. Other variables such as firm size, book to market equity ratio, debt equity ratio and earning yield are found to be insignificant variables to explain variation in cross-section returns